Nutritive evaluation of differently processed mucuna seeds for ruminants (2017)
Mucuna as a feed has great ability to serve as a source of energy and protein in dry season feeds due to the fact that it has high crude protein content comparable to other well known legumes. The study was designed to evaluate the nutritive compositions of Mucuna beans subjected to various treatments: roasting, boiling, autoclaving and raw. Thereafter, the proximate composition, invitro gas production and fermentative characteristics of the treated beans were undertaken. Result showed significant differences in the roasted beans for dry matter (DM) and crude protein (CP) values of 96.97 and 36.86 %, respectively. Other proximate parameters (crude fibre, ash and nitrogen free extract) were similar for all treated beans. In vitro gas production after 24 hours showed that autoclaved (32.75 mL), boiled (32.25 mL) and raw beans (29.75 mL) were similar (p>0.05) and more utilizable as ruminant feed compared to the roasted form. Roasted beans recorded the least (11. 00 mL) gas production. Roasting affected the fermentation characteristics significantly (p<0.05) by lowering its organic matter digestibility (OMD, 42.20 % DM), short chain fatty acids (SCFA, 0.31 mmol/L), metabolizable energy (ME, 5.71 MJ/Kg DM) and methane gas (MG, 7.75 mL/200 mg DM). Roasting perhaps affected the fibre structure thereby making it unavailable for microbes to act on as evident in results from in vitro gas production and fermentative characteristics. However, other treatments (excluding raw) posits a potentiality of Mucuna as a source of energy for ruminants' especially in dry season when there is scarcity of dietary energy sources.